Investigating the Effects of Ibuprofen on the Gene Expression Profile in Hippocampus of Mice Model of Alzheimer’s Disease through Bioinformatics Analysis - Zamanian-Azodi, Mona (Iran J Pharm Res, 2020)
Non-steroidal anti-inflammatory drugs (NSAIDs) are identified as effective in many diseases. One of which is neurodegenerative diseases including Alzheimer disease (AD). In this study gross alteration of gene expression in AD mice by ibuprofen treatment is investigated via Protein-protein interaction network (PPI) analysis. Expression profiling of microarray dataset GSE67306 was retrieved from GEO database and analyzed via GEO2R tool. PPI analysis was performed via Cytoscape 3.7.0. and its plug-ins including Network Analyzer, Gene MANIA, and CluePedia. Numbers of 10 central genes including Htr1a, Sstr2, Drd2, Htr1b, Penk, Pomc, Oprm1, Npy, Sst, and Chrm2 were identified as potential biomarkers. However, the role of Penk gene was highlighted. The finding indicates that ibuprofen changes gene expression level of several genes that are involved in AD.